Cost-effectiveness in anaesthesia: Inhalation or total intravenous anaesthesia - Erhan, Ömer L.; Yaşar, M. Akif; Bayar, M. Kemal; Gün, Ash; Akin, Mustafa (My University, 2002)
Nowadays because of the wide spectrum of drugs and the commercial presentation forms of them which are whether used for inhalational anaesthesia (IA) or total intravenous anaesthesia (TIVA) are being interrogated for cost effectiveness. In this study indirect cost of frequently used anaesthetic methods are compared. After getting approval from the ethic committe 333 ASA-I-II class patients randomly received TIVA (n=209) or IA (n=124). 10 groups were classified due to contents of anaesthetic agent's commercial mg or mL form. Indirect cost related to anaesthetic methods were compared by using Mann-Whitney U test. It has been seen that indirect cost in TIVA groups which use midazolam was less than the TIVA groups which use propofol and also less than sevoflurane groups. Isoflurane group provided significant economic cost effectivenes compared to evoflurane groups (p<0.001). This low cost was little compared with midazolam groups and a lot compared with propofol groups but was not statistically significant (p>0.001). As a conclusion; more cheaper anaesthetic methods can be formed via different anaesthetic drugs and combination of them.
Anestezide maliyet-etkinlik: Inhalasyon veya total intravenöz anestezi
Keywords: Cost-effectiseness anaesthesia; Inhalation; TIVA